Climate changes affecting global iodine status - Peter PA Smyth; Colin D O’Dowd (European Thyroid Journal, 2024)
Global warming is now universally acknowledged as being responsible for dramatic climate changes with rising sea levels, unprecedented temperatures, resulting fires and threatened widespread species loss. While these effects are extremely damaging, threatening the future of life on our planet, one unexpected and paradoxically beneficial consequence could be a significant contribution to global iodine supply. Climate change and associated global warming are not the primary causes of increased iodine supply, which results from the reaction of ozone (O3) arising from both natural and anthropogenic pollution sources with iodide (I−) present in the oceans and in seaweeds (macro-and microalgae) in coastal waters, producing gaseous iodine (I2). The reaction serves as negative feedback, serving a dual purpose, both diminishing ozone pollution in the lower atmosphere and thereby increasing I2. The potential of this I2 to significantly contribute to human iodine intake is examined in the context of I2 released in a seaweed-abundant coastal area. The bioavailability of the generated I2 offers a long-term possibility of increasing global iodine status and thereby promoting thyroidal health. It is hoped that highlighting possible changes in iodine bioavailability might encourage the health community to address this issue.